2021
DOI: 10.1136/bmjopen-2021-052899
|View full text |Cite
|
Sign up to set email alerts
|

Patient outcomes and cost savings associated with hospital safe nurse staffing legislation: an observational study

Abstract: ObjectiveTo evaluate variation in Illinois hospital nurse staffing ratios and to determine whether higher nurse workloads are associated with mortality and length of stay for patients, and cost outcomes for hospitals.DesignCross-sectional analysis of multiple data sources including a 2020 survey of nurses linked to patient outcomes data.Setting: 87 acute care hospitals in Illinois.Participants210 493 Medicare patients, 65 years and older, who were hospitalised in a study hospital. 1391 registered nurses employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…Internationally, the implementation of mandated patient-to-nurse ratios is widely debated to achieve safe staffing levels. Although the business case is taking shape, [ 12 , 41 , 42 ] only a limited number of regions have mandated ratios (e.g. Victoria/Queensland in Australia and California in the USA).…”
Section: Discussionmentioning
confidence: 99%
“…Internationally, the implementation of mandated patient-to-nurse ratios is widely debated to achieve safe staffing levels. Although the business case is taking shape, [ 12 , 41 , 42 ] only a limited number of regions have mandated ratios (e.g. Victoria/Queensland in Australia and California in the USA).…”
Section: Discussionmentioning
confidence: 99%
“…The unfunded mandate resulted in patients in California hospitals currently receiving, on average, 2-3 more hours a day of registered nurse care than patients in other states ( Dierkes, et al, 2021 ). Similar safe nurse staffing legislation has been considered in other states but despite research estimating improved patient outcomes and cost savings ( Lasater, et al, 2021a ; Lasater, et al, 2021b ), no other states have implemented minimum hospital nurse staffing requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Although regression models explained 41% of LOS variation, evidently, factors not included in the data greatly influence LOS. Whilst staffing ratios may be a factor [ 37 ], their attributable weighting is unclear. Moreover, many administrative datasets do not provide standardised reporting; therefore, minimum data sets and indicator development should seek to harmonize across jurisdictions [ 38 ], since a review of palliative care costing in the UK [ 39 ] suggested lacking data has implications on how palliative care (and palliative care research) is planned and funded.…”
Section: Discussionmentioning
confidence: 99%